ANALISIS LOKASI PEMBUANGAN LIMBAH PADAT DI KOTA TEGAL MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Iryanthony, Sigit Bayhu (Universitas Pendidikan Ganesha, 2018)
The increasing population population is a problem for the environment. Increased population will increase the amount of consumption and waste generated. Waste Solid (SW) becomes a problem that is not needed properly. SW deliber changes environmental balance that can cause contamination of soil, air and air. The problem of SW in Tegal City becomes a serious problem. TPA located in Muarareja Urban Village, the lease of the land has expired since November 2015. The need to study the determination of the landfill location is an immediate need. By utilizing Geographic Information System (GIS), is an ideal model in determining location based on data overlay method. GIS utilization with physical data analysis and conformity with Spatial Plan (RTRW). Obtained several location options that can be used as an alternative landfill location. Some government locations, 1) Pulosari District, Kab. Pemalang, 2) District Tonjong, Kab. Brebes, 3) Kedungbanteng Sub-district, Tegal Regency.